Regional odontodysplasia: Report of an unusual case involving mandibular arch - N S Venkatesh Babu; R Jha Smriti; D Bang Pratima (Wolters Kluwer Medknow Publications, 2015)
Regional odontodysplasia (RO) is a rare developmental anomaly involving both mesodermal and ectodermal components in primary or permanent dentition. It affects the maxilla and the mandible or both; however, maxilla is more commonly involved. This article reports the case of 33-month-old boy who came with the chief complaint of delayed eruption of mandibular teeth. Findings of clinical and radiographic examination were consistent with those of RO. Maxillary dentition was unaffected. Clinical and radiographic features and treatment options are discussed.